A Simple and Validated Reverse Phase HPLC Methodfor the Determination of Rabeprazole inPharmaceutical Dosage Forms - Uma Mahesh Karra; Sanjeeva Yarkala (E-Journal of Chemistry)
A simple and rapid reverse phase high performance liquid chromatography (RP-HPLC) method was developed and validated for quantitative determination of rabeprazole in bulk drug samples and formulations. Rabeprazole was analyzed by using reverse phase LC-GC column (Inertsil ODS, 4.6 mm x 25 cm, 5 microns), with mobile phase consisting of methanol: water (78:22 v/v). The flow rate was set 1.0 mL/min and analysis was performed at wavelength 288 nm using Photo Diode Array (PDA) detector at ambient temperature. The method was validated and stability studies were conducted under different conditions. The retention time for rabeprazole was around 4.12 minutes. The calibration curves were linear (r≥0.9998) over a concentration range from 20.0 to 80.0 μg/mL. Limit of detection (LOD) and Limit of quantitation (LOQ) were 8 ng/mL and 24 ng/mL respectively. The developed method was successfully applied to estimate the amount of rabeprazole in tablet formulations.